CONSAL at the crossroads challenges for a greater regional cooperation : 13th general conference : Congress of Southeast Asian Librarians (CONSAL), 25-30 March 2006, EDSA Shangri-la Hotel, 1 Garde Way Ortigas Center, Mandaluyong City Metro Manila, Philippines - Congress of Southeast Asian Librarians 2006 : Manila); CONSAL Executive Board (Manila : CONSAL Executive Board, 2006)
Contained the abdtract of work papers, programme and organizing committee and also resource of the speaker in PDF format
Keywords: Library science -- Southeast Asian -- Congresses; Library science -- Developing countries -- Congresses